Correlates of neutrophil/lymphocyte, platelet/lymphocyte, and platelet/neutrophil ratios of neonates of women with hypertensive disease of pregnancy with neonatal birth outcomes. (3rd April 2019) - Okoye, Helen Chioma; Madu, Anazoeze Jude; Korubo, Kaladada; Efobi, Chilota; Eze, Onyinye Ezinne; Obodo, Onochie; Okereke, Kelechi; Ilechukwu, Gladys
ABSTRACT: Background : Studies have indicated neutrophil/lymphocyte ratio (NLR), Platelet/Lymphocyte ratio (PLR), and platelet/neutrophils ratio (PNR) to be inflammatory markers. The correlation of these values in infants of hypertensive mothers has not been investigated. Aim : To investigate the relationship between NLR, PLR, and PNR of neonates of women with hypertensive disease of pregnancy and neonatal APGAR scores and birth weight. Methodology : Cord blood samples of 200 neonates collected and the blood counts and ratios obtained. Results : NLR in the babies of the hypertensive mothers was 0.865 and 1.42 in the control group ( p = 0.0001). PLR was 34.7 in the neonates of the hypertensive mothers and 62.4 in the control group ( p = 0.0001). PNR did not differ significantly between the two groups, p = 0.418. Degree of hypertension had a direct relationship with NLR; SBP had a p value of 0.001 while the DBP had p = 0.002. The PLR had an inverse relationship with the degree of hypertension; SBP p value of 0.0001, while DBP was p = 0.0001. No significant association was observed between the ratios and neonatal birth weight ( p ≥ 0.05); however, PNR and PLR were found to be significantly associated with the 1st ( p = 0.045 and 0.030) and 5th (0.049 and 0.037) minute APGAR scores in the newborns. Conclusion : PLR and NLR in neonates of hypertensive mothers are found to be markedly lower than those of controls, the degree of which is affected by the severity of hypertension. Also, lower PLR is associated with lower APGAR scores. Therefore, severity of high blood pressure and lower PLR may be determinants of poor birth outcome.